Human Papillomavirus - Rajkumar, Rajamanickam (IntechOpen, 2020)
This book is about the highly infective human papilloma virus (HPV). There are more than 200 strains of HPV, though only a few, like HPV 16 and HPV 18, are oncogenic. HPV infections can lead to cancers of the cervix, vulva, vagina, anus, penis, and oral cavity.Written by authors from across the globe, this book is a comprehensive look at HPV. Chapters cover such topics as the epidemiology of HPV, treatment of the manifestations of HPV, which can include warts on the skin and genitals, diagnosis and management of oral mucosal cancers due to HPV, HPV and pregnancy, and HPV vaccines. It is a useful reference for researchers and scientists in the field, providing them with helpful knowledge to combat and prevent HPV infections and cancers.